2003
DOI: 10.1002/ijc.10904
|View full text |Cite
|
Sign up to set email alerts
|

GLUT‐1 and CAIX as intrinsic markers of hypoxia in carcinoma of the cervix: Relationship to pimonidazole binding

Abstract: The presence of hypoxia in tumours results in the overexpression of certain genes, which are controlled via the transcription factor HIF-1. Hypoxic cells are known to be radioresistant and chemoresistant, thus, a reliable surrogate marker of hypoxia is desirable to ensure that treatment may be rationally applied. Recently, the HIF-1-regulated proteins Glut-1 and CAIX were validated as intrinsic markers of hypoxia by comparison with pO 2 measured using oxygen electrodes. We compare the expression of Glut-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
161
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(174 citation statements)
references
References 37 publications
(41 reference statements)
9
161
0
2
Order By: Relevance
“…Glucose transporter and ADM also showed significant correlation with each other. Glucose transporter 1 protein immunohistochemistry has previously been shown to correlate with CA IX staining in cervical cancer and, like CA IX, it has been shown to be a marker of tumour hypoxia (Airley et al, 2001(Airley et al, , 2003. The correlation here shows that the same is also likely to be true for bladder cancer.…”
Section: Discussionsupporting
confidence: 63%
“…Glucose transporter and ADM also showed significant correlation with each other. Glucose transporter 1 protein immunohistochemistry has previously been shown to correlate with CA IX staining in cervical cancer and, like CA IX, it has been shown to be a marker of tumour hypoxia (Airley et al, 2001(Airley et al, , 2003. The correlation here shows that the same is also likely to be true for bladder cancer.…”
Section: Discussionsupporting
confidence: 63%
“…The extent of a positive correlation between immunohistochemical staining results for these markers is the subject of a controversial discussion. Although Olive et al (2001) found a very strong correlation (r ¼ 0.86, n ¼ 14) in human cervical cancer, Airley et al (2003) did not find a significant correlation (r ¼ 0.27; P ¼ 0.083, n ¼ 42). In head and neck cancer, Kaanders et al (2002) found a weak, but significant correlation (r ¼ 0.36; P ¼ 0.02, n ¼ 42).…”
Section: Discussionmentioning
confidence: 89%
“…To date, various methods are available to measure tumour oxygenation, including polarographic oxygen sensors (Vaupel et al, 1991), luminescence-based optical sensors (Bussink et al, 2000) and antibody-based detection of exogenous (Haustermans et al, 2000;Raleigh et al, 2001;Koch, 2002) and endogenous markers of hypoxia (Wykoff et al, 2000;Janssen et al, 2002;Airley et al, 2003). At this time, only the polarographic oxygen-sensor and the exogenous hypoxia marker pimonidazole (PIMO) can be considered as 'standard'.…”
mentioning
confidence: 99%
“…Several studies have attempted to achieve this goal. Airley et al (2003) undertook a direct comparison of all three markers in cervix cancer specimens. The study concluded that there were similar staining patterns for all three markers and that they were significantly correlated with each other, although this comparison was made on a semiquantitative scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two proteins, carbonic anhydrase IX (CAIX) and glucose transporter-1 protein (GLUT1), have received much recent attention (Airley et al, 2001(Airley et al, , 2003Chia et al, 2001;Giatromanolaki et al, 2001;Loncaster et al, 2001;Olive et al, 2001;Swinson et al, 2003). In an initial series of bladder cancers, CAIX was found to colocalise with pimonidazole (Wykoff et al, 2000).…”
mentioning
confidence: 99%